Pleural Paragonimiasis in an HIV-Positive Patient with Tuberculosis: An Incidental Finding of Paragonimus westermani on Histopathology - Ali Masoud; Marey Alhajji; Rema Saad; Tareq Lehmidi; Warda Said (AlQalam Journal of Medical and Applied Sciences, 2025)
HIV, TB, and pleuropulmonary paragonimiasis co-infection is extremely rare and presents a significant diagnostic challenge due to superimposed clinical and radiological findings. Immunological suppression induced by HIV predisposes individuals to tuberculosis (TB) and concurrently suppresses the typical parasitic immune response, such as eosinophilia. Paragonimus westermani is the sole causative agent of human paragonimiasis, a disease endemic in Asia and Africa, predominantly transmitted through the consumption of raw or inadequately cooked freshwater crustaceans. We present the case of a 29-year-old Libyan male patient with a known history of HIV infection and established pulmonary TB. The patient is presented with chronic cough, weight loss, pyrexia, and pleuritic chest pain. Imaging showed chronic pleural effusion and thickening. While the patient was confirmed to have TB via GeneXpert, a VATS-guided pleural biopsy unexpectedly detected parasitic ova that are consistent with P. westermani. Histopathological diagnosis, utilizing special stains (Giesma), was essential as peripheral eosinophilia was not evident. The patient clinically improved following anti-tuberculous therapy, even though anti-parasitic therapy was not administered due to early discharge. This case highlights the importance of including parasitic infection in the differential diagnosis for unresponsive effusions in an immunocompromised host, particularly in endemic locations. Early histopathology and biopsy are valuable in unusual instances to prevent misdiagnosis and delayed treatment.